Banknote authentication using artificial neural network - Mohamad, Nur Syuhada; Hussin, Burairah; Shibghatullah, Abdul Samad; Hasan Basari, Abd Samad (Publications International, 2014)
Counterfeit banknote is an imitation currency produced without the legal sanction of the state or government. This paper is focusing on how to classify the detection technique of counterfeit banknotes. The approach that will be implemented to solve this problem is by using the method of Artificial Neutral Network. In this research, the author prefers to use back-propagation training in Artificial Neural network. The instrumentation used, is the MATLAB’s GUI application that will be designed and developed to examine and identify the authentication of banknotes. The sample data was provided by the Center of Machine Learning and Intelligent System database. In the process to get the result, the author decides to classify this sample of banknotes data into training, testing and validation.